PHRASEOLOGICAL TRANSFORMANTS AND THEIR MODELLING IN UZBEK LANGUAGE (Scientific journal of the Fergana State University, 2023)
The purpose of this article is to reveal the phenomenon of phraseological transformation by highlighting the structural-semantic structure of lexical phraseologisms of the Uzbek language, their syntagmatic implementation in the speech environment.It uses scientific methods such as description, comparison, classification, modelling and differential-semantic.The questions of determining the ways of formation types - expansion, contraction, exchange and mixed type of derivative units, in particular transformants formed as a result of changes in phraseological phrases of the Uzbek language in the speech environment, and their modelling are analysed.